Estimated 8-year cumulative incidence of diabetes mellitus among Sami and non-Sami inhabitants of Northern Norway - The SAMINOR Study - Naseribafrouei, Ali; Eliassen, Bent Martin; Melhus, Marita; Svartberg, Johan; Broderstad, Ann Ragnhild (BMC Endocrine Disorders, 2019)
Source at https://doi.org/10.1186/s12902-019-0399-7. © The Author(s). 2019 Background : The aim of the study was to estimate and compare the 8-year cumulative incidence of diabetes mellitus (DM) among Sami and non-Sami inhabitants of rural districts in Northern Norway. Methods : Longitudinal study based on linkage of two cross-sectional surveys, the SAMINOR 1 Survey (2003–2004) and the SAMINOR 2 Clinical Survey (2012–2014). Ten municipalities in rural Northern Norway were included in the study. DM-free participants aged 30 and 36–71 years in SAMINOR 1 were followed from 2 years after SAMINOR 1 to attendance in SAMINOR 2. The average follow-up time was 8.1 years. Of 5875 subjects who had participated in SAMINOR 1 and could potentially be followed to SAMINOR 2, 3303 were included in the final analysis. Self-reported DM and/or HbA1c ≥ 6.5% were used to identify incident cases of DM. Results : At baseline, body mass index (BMI) and waist-to-height ratio (WHtR) were higher among Sami than among their non-Sami counterparts. After 8 years of follow-up, 201 incident cases of DM were identified (6.1% both Sami and non-Sami subjects). No statistically significant difference was observed in the cumulative incidence of DM between the Sami and non-Sami. Conclusions : No statistically significant difference in the 8-year cumulative incidence of DM among Sami and nonSami was observed, although Sami men and women had higher baseline BMI and WHtR.